2021
DOI: 10.1080/21645515.2020.1846396
|View full text |Cite
|
Sign up to set email alerts
|

Immune memory: an evolutionary perspective

Abstract: The innate immune system, through pattern recognition receptors, intercepts any kind of pathogen and reacts through chemotactic, phagocyting, cytokines-secreting and cell-killing mechanisms in a very quick and effective way. Meanwhile, the adaptive immunity arm, through dendritic and T and B cells memory activation, is alerted and starts, more slowly, to produce antibodies, seen thanks to the progress of immunological investigations in comparative vertebrates, invertebrates, and vegetal models.However, it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The particular experimental design utilised here allowed us to examine whether PL may be involved in the long-term maintenance of contextual fear memories. This advances previous knowledge which suggests this region is essential for the expression of contextual fears (see review by Rozeske et al, 2015 and research studies by Frankland et al, 2004;Corcoran and Quirk, 2007;Laurent and Westbrook, 2008;Goshen et al, 2011;Stevenson, 2011;Stern et al, 2013), but not the formation of contextual fears (Morgan et al, 1993;Morrow et al, 1999b;Fernandez Espejo, 2003;Antoniadis and McDonald, 2006;Bissière et al, 2008). However, the ability to accurately study fear expression vs. fear maintenance is difficult.…”
Section: Technical Considerationsmentioning
confidence: 52%
See 3 more Smart Citations
“…The particular experimental design utilised here allowed us to examine whether PL may be involved in the long-term maintenance of contextual fear memories. This advances previous knowledge which suggests this region is essential for the expression of contextual fears (see review by Rozeske et al, 2015 and research studies by Frankland et al, 2004;Corcoran and Quirk, 2007;Laurent and Westbrook, 2008;Goshen et al, 2011;Stevenson, 2011;Stern et al, 2013), but not the formation of contextual fears (Morgan et al, 1993;Morrow et al, 1999b;Fernandez Espejo, 2003;Antoniadis and McDonald, 2006;Bissière et al, 2008). However, the ability to accurately study fear expression vs. fear maintenance is difficult.…”
Section: Technical Considerationsmentioning
confidence: 52%
“…In contrast, research studies on the mPFC suggest it plays a different role (Fanselow, 2010;Gilmartin et al, 2014;Rozeske et al, 2015). Studies have demonstrated that inhibition, damage, manipulation or removal of the mPFC prior to CFC to have no effect on subsequent fear-related freezing to context (Morgan et al, 1993;Morrow et al, 1999b;Fernandez Espejo, 2003;Antoniadis and McDonald, 2006;Bissière et al, 2008). However, the involvement of the mPFC, or more specifically, the PL, in the expression of these contextual fear memories is well documented (see review by Frankland et al, 2004;Corcoran and Quirk, 2007;Laurent and Westbrook, 2008;Goshen et al, 2011;Stevenson, 2011;Stern et al, 2013;Rozeske et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, however, conclusive evidence has accumulated demonstrating that innate immunity may also possess some adaptation ability. It recognizes and remembers the non-self, the foreign molecular patterns not only in vertebrates but also in invertebrates [ 7 , 8 , 9 , 10 ], and even in plants, and is termed “systemic acquired resistance” [ 11 , 12 , 13 ] (for review, see Gourbal et al, 2018 [ 14 ]).…”
Section: Types Of Immunity Of Multicellular Organismsmentioning
confidence: 99%